2021
DOI: 10.3233/wor-205045
|View full text |Cite
|
Sign up to set email alerts
|

Prevention measures and risk factors for COVID-19 in Iranian workplaces

Abstract: BACKGROUND: Exposure to the coronavirus (COVID-19) in industrial workplaces has caused concerns all over the world. Implementation of prevention measures is the best solution for protection of workers’ health. OBJECTIVE: The present study investigated prevention measures and risk factors for the COVID-19 infection in Iranian small, medium, and large industries. METHODS: This study was conducted on 349 occupational health, safety, and environment professionals working in different industries. Data was collected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…This increment has various reasons in each country. In Iran, wrong decisions at the national level caused an increased number of gatherings in different places, such as shops, public transportation, banks, government offices, industrial settings, and other similar venues [34,35]. Lack of proper programs for children and the elderly; monopoly on the distribution of essential foods leading to gathering in front of related shops; accumulation in clinics of medical centers and hospitals, medical offices, and private clinics at specific hours; closure of open-air public parks leading to gathering in closed places, lack of affordable face masks; and non-observance of prevention protocols by most people [34] were among the most important reasons of high mortality.…”
Section: Discussionmentioning
confidence: 99%
“…This increment has various reasons in each country. In Iran, wrong decisions at the national level caused an increased number of gatherings in different places, such as shops, public transportation, banks, government offices, industrial settings, and other similar venues [34,35]. Lack of proper programs for children and the elderly; monopoly on the distribution of essential foods leading to gathering in front of related shops; accumulation in clinics of medical centers and hospitals, medical offices, and private clinics at specific hours; closure of open-air public parks leading to gathering in closed places, lack of affordable face masks; and non-observance of prevention protocols by most people [34] were among the most important reasons of high mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Research shows that personal protective measures (e.g., physical distancing, hand hygiene, and maskwearing) are considered as one of the main public health and social measures (PHSMs) that should be implemented in order to suppress COVID-19 transmission [19,20]. The importance to using masks, handwashing, social distancing, maintaining a healthy lifestyle, conducting tracing, tracking, and testing provide significant COVID-19 cases from the workplace [3,6,[12][13][14][15][16][17][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37].…”
Section: Implementation Of Health Protocolsmentioning
confidence: 99%
“…It was reported that the larger the size of the company, the more measures are implemented in Italy, Japan, and Iran. 7 , 8 , 9 It was also reported that the financial sector took more progress measures than the food sector in Italy. 7 However, to the best of our knowledge, the impact of factors related to workplace health cultures, such as workplace health promotion policies and practices, has not been examined.…”
Section: Introductionmentioning
confidence: 99%
“…There are significant differences among workplaces in the implementation of infection control measures. It was reported that the larger the size of the company, the more measures are implemented in Italy, Japan, and Iran 7–9 . It was also reported that the financial sector took more progress measures than the food sector in Italy 7 .…”
Section: Introductionmentioning
confidence: 99%